Analisis Losses Pada Boiler Feed Pump PLTU Muara Karang Unit 5 - Vendy Antono; Adi Gunawan (JURNAL POWERPLANT, 2013)
Center Steam Power (power plant) is a type of power plant that is the most common and most of the electrical energy needs on the island of Java and Bali are supplied by the plant species. Broadly speaking, the system of steam power plant (power plant) is composed of some major equipment and support equipment. One part of the steam power generation equipment that plays a key role is the Boiler Feed Pump (BFP). BFP main function is to pump the fluid from the deaerator heading to Steam Boiler Drum through through High Pressure Heater and economizer. BFP in Muara Karang power plant unit 5 uses an electric motor as a pump drive and media use as transmission fluid coupling of the pump. BFP magnitude greatly affect the efficiency losses (losses) of the component - the component. Therefore, the magnitude of losses (losses) that occur need to be analyzed to gain efficiencies actual Boiler Feed Pump. This research aims to study and analyze the depth of the losses in the system BFP (Boiler Feed Pump). The results are used to determine the value of losses on some components of the system BFP. The results showed that the value of the copper losses and the loss of magnetization of electric motors at 216.051 kJ, losses due to fluid friction in the pump for 1424.8694 kJ, the losses can not be taken into account such as the pump bearings, clutch bearings, motor bearings, radiation and Lubricate the coupling of 262.3645 kJ.